(untitled) (Research, Society and Development, 2020)
The riparian forest is present along with watercourses and is characterized by high environmental heterogeneity. This research aims to evaluate the arboreal community diversity of the Paraguay River riparian forest, in areas of plateau and plain, in the northern portion. For data collection, six modules were established with five disjoint plots of 20m x 100m, totaling one hectare in each module. The inclusion level consisted of specimen’s diameter ≥ 5 cm, measured at 1.30 m above the ground, and ≥ 3 m height. Six hectares were sampled, where 4,749 specimens belonging to 52 botanical families, 119 genera and 167 species were measured. The richness was significantly higher in the plateau, transition region between Cerrado and Amazon, and in the region of the confluence of rivers, a heterogeneous region that expresses the Cerrado and Amazon with regions of enclosures in the Pantanal, differing from the plain lower richness, but both areas have high biological and ecological value.